Evaluation of various rice (Oryza sativa) based crop sequences for enhanced productivity, profitability and energy efficiency in eastern plateau and hills zone of India - MISHRA, M M; MOHANTY, M; GULATI, J M L; NANDA, S S (The Indian Journal of Agricultural Sciences, 2026)
A field experiment was conducted consecutively for four years (2004-05 to 2007-08) at Regional Research Station, Chiplima (Sambalpur), Odisha on sandy loam soil with pH 6.0 and organic carbon content of 0.56%. The available N, P and K were 212, 15.7 and 89 kg/ha respectively. The experiment was laid out in randomized block design involving 1 rice based crop sequences with three replications. Among various cropping sequences evaluated, rice (Oryza sativa L.) frenchbean(Phaseolus vulgaris)-greengram (Vigna radiata L.) produced the highest rice equivalent yield (17.31 tonnes/ ha/year), net return (Rupees 39 899/ha), benefit: cost ratio (2.25) and monetary advantage (140.48 Rupees /ha/day). This system was the most sustainable with sustainable yield index of 0.40 and sustainable value index of 0.84 with higher energy productivity (0.854 kg/MJ) and energy intensiveness (0.078 MJ/Re). However, the rice- groundnut-sesame system had highest land use efficiency of 87.14% whereas rice-radish-greengram registered the highest production efficiency (61.54 kg/ha/day). Rice- groundnut - greengram sequence was found to be the most efficient user of N (138.8 kg yield/ha N applied) whereas rice - groundnut - fallow used P (388.3 kg yield/ha N applied) and K (202.6 kg yield/ha N applied) more efficiently than that of other cropping sequences. The study further revealed that rice productivity could be enhanced by 19.1 and 17.7% due to inclusion of oilseeds and pulses, respectively than that of its monocropping..